The Effectiveness of Visual Picture Economics Textbook Based on Problem Based Learning in Improving Reading Literacy Skills - Setyowati, Fitri Andriani; Kristiani; Murwaningsih, Tri (Journal of Education Technology, 2022)
The low reading literacy of Indonesian students is still a problem in the world of education in Indonesia. Testing the feasibility of reading literacy instruments and testing the effectiveness of visual picture economics textbook based on problem-based learning in improving reading literacy skills are the objectives of this study. This type of study is quasi-experimental, with a sample of 62 students divided into classes XI IPS1 and XI IPS2. The samples in this study used the cluster random sampling method. The data taken from this study used various techniques including (1) interviews, (2) observations, (3) questionnaires, and (4) questions. Data analysis uses several techniques including (1) quantitative descriptive analysis, (2) Inferential statistical analysis was preceded by a prerequisite test consisting of a normality test and a homogeneity test followed by a t-test, and (3) hypothesis testing. The results showed that the reading literacy instrument was declared feasible and valid, and the research data were normally distributed and homogeneous. In addition, based on the t-test, the results showed that H0 was rejected and H1 was accepted, which means that there is a difference in the level of students' reading literacy skills between using visual picture economics textbook based on problem-based learning and conventional economics textbooks. In the experimental class, the average reading literacy level was 68.74 and 60.52 in the control class. Based on these results, the use of an economic textbook with visual images based on problem-based learning is more effective in improving reading literacy compared to using conventional economics textbooks. This research implies increasing reading literacy skills by utilizing visual picture economics textbook based on problem-based learning.